Machine learning and interpretation in neuroimaging : 4th International Workshop, MLINI 2014, held at NIPS 2014, Montreal, QC, Canada, December 13, 2014, Revised selected papers /: 4th International Workshop, MLINI 2014, held at NIPS 2014, Montreal, QC, Canada, December 13, 2014, Revised selected papers. (2016) - Unknown
No abstract available